Preparation and Relevance of the Qualitative Consistency Matrix for Research in the Social Sciences - Giesecke Sara Lafosse, Mercedes P. (2020)
This work is a contribution for researchers and social sciences thesis students who seek to apply a qualitative approach to their research projects. The Qualitative Consistency Matrix (MCC) is proposed as a methodological instrument that makes it possible to systematize, analyze and understand the procedures and advances of research involving phenomena, events, situations and subjects that differ in their nature and structure from those objects and topics addressed via a quantitative approach, in contrast to the design, structuring and operationalization of variables in order to validate the relevance and feasibility of a research project, which is summarized in the verification and development of the Quantitative Consistency Matrix (MCC), or deductive logical matrix.